Simulation of a multi-source hybrid heat pump system with seasonal thermal storage in cold regions. (April 2017) - Han, Zongwei; Qu, Lejian; Ma, Xiao; Song, Xiaobei; Ma, Changming
Highlights: A novel multi-source hybrid heat pump system with seasonal thermal storage is constructed. Mathematical model of the heating and air conditioning system was established. The performance of the multi-source hybrid heat pump system and ground source heat pump system is simulated and compared. The applicability of the multi-source hybrid heat pump system in different climate regions is investigated. Abstract: Based on taking full account of the building load and renewable energy output characteristics in cold regions, a multi-source hybrid heat pump system (MSHHPS) with seasonal thermal storage was proposed. The seasonal thermal storage comprehensively utilized solar energy, geothermal energy and air energy. The composition and operation modes of the system were introduced. The mathematical model of the main parts of the proposed system was established. The transition condition of the different operating modes of the system was determined. Taking a building in Harbin as the object for simulation analysis, the operation effect and the change of the soil temperature field of the system were obtained. The results showed that: The average coefficient of performance ( COP ) of the MSHHPS with seasonal thermal storage was 3.06 (in the Harbin region for 10 years), the soil thermal balance rate was 100.33% and the energy-saving rate was 29.84% comparing to the ground source heat pump system (GSHPS). For the initial investment, MSHHPS only required additional double-source heat pump unit, which accounted at 9.59%. The static payback period of the double-source heat pump unit was 4 years. The system can maintain efficient and economical operation in the typical cold regions.